Characteristic of aroma components and antioxidant activity of essential oil from Ocimum tenuiflorum leaves. (18th May 2022) - Kunihiro, Kento; Kikuchi, Yuta; Nojima, Satoshi; Myoda, Takao
Abstract: Ocimum tenuiflorum has a characteristic spicy, sweet and green aroma and has been used as a medicinal herb for various diseases in Ayurveda systems. This study aimed to investigate the aroma‐impact components and antioxidant activity of the essential oil from O. tenuiflorum leaves, grown in Sri Lanka, which was obtained by hydrodistillation. The volatile compounds in the essential oil were measured by gas chromatograph–mass spectrometry. The major components were caryophyllene oxide (23.8%), β‐caryophyllene (18.2%), germacrene D (14.6%), α‐copaene (14.4%) and eugenol (10.0%). The characteristics of aroma components of the essential oil were determined by gas chromatography–olfactometry and aroma extract dilution analysis. Eleven compounds, including eugenol, rotundone, β‐damascenone, linalool and geraniol, were identified as aroma‐impact components of the essential oil. Among them, the dominant components were identified as eugenol, rotundone, 3‐hydroxy‐4, 5‐dimethyl‐2(5 H )‐furanone, coumarin and vanillin, which were quite different from the results of chemical analysis. The antioxidant activity of the essential oil was evaluated by 1, 1‐diphenyl‐2‐picrylhydrazyl radical scavenging activity, 2, 2′‐azino‐bis (3‐ethylbenzothiazoline‐6‐sulfonic acid) radical cation scavenging activity and β‐carotene bleaching assays. All results showed that the essential oil exhibited strong antioxidant activity, and antioxidant‐active components were proved to be eugenol by column chromatography. Furthermore, the presence of new antioxidant compounds other than eugenol, which had previously been reported, was also revealed. Therefore, the essential oil from O. tenuiflorum leaves has great potential as a resource in the cosmetics and food industries. Abstract : Characteristic of aroma components and antioxidant activity of essential oil from Ocimum tenuiflorum leaves were investigated. Eleven compounds were identified as aroma‐impact components. The essential oil also showed a very strong antioxidant activity. Our findings indicate that the essential oil may be promising natural sources for cosmetics and food additives.